EPIDEMIOLOGICAL STATUS AND CLINICAL PROFILE OF ACCIDENTAL CHILDHOOD POISONING CASES ADMITTED IN A TERTIARY CARE HOSPITAL OF EASTERN INDIA WITH SPECIAL REFERENCE TO AWARENESS OF PARENTS - MISRA, SHILADITYA; PUITANDI, SAMPRITI; BISWAS, LINKON; BISWAS, KOUSTAV; GHOSH, TARAPADA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Accidental poisoning is one of the major medical emergencies in paediatric population, specially among under five children. However, there is still lack of clinicodemographic data mostly due to under-reporting of events. In this study, we analyzed the clinicoepidemiological profile as well as awareness of parents in respect to childhood poisoning cases admitted in our institute. Methods: Children aged up to 12 years admitted in our hospital with accidental poisoning between January 2020 to June 2021 were included in this study. We collected their demographic, epidemiological and clinical data, analyzed, and compared these with data from other parts of India as well as world. Results: About 87% of children were under 5 years of age with a male dominance (male: female was 1.3:1). Majority of children (65%) were from lower socioeconomic class and 66% of parents had no knowledge or ignorant about the poisonous substance. Hydrocarbons like-kerosene oil (44.5%) followed by drugs were the most common substance related to poisoning. Cough (23.7%) followed by vomiting (21%) was the most common presenting symptom and cardiorespiratory abnormalities were most common (49%) finding on clinical examination. About 5% of children died due to poisoning or its related effects. Conclusion: It can be said that negligence and ignorance from the side of caregivers play the most important role in such calamities. Community-based childhood poisoning prevention program and simple preventive measures like education to the parents, proper storage of household items, and proper placement of drugs could be helpful in preventing mortality and morbidity in children with poisoning.